Vaccine effectiveness of primary series and booster doses against covid-19 associated hospital admissions in the United States: living test negative design study. (11th October 2022) - Adams, Katherine; Rhoads, Jillian P; Surie, Diya; Gaglani, Manjusha; Ginde, Adit A; McNeal, Tresa; Talbot, H Keipp; Casey, Jonathan D; Zepeski, Anne; Shapiro, Nathan I; Gibbs, Kevin W; Files, D Clark; et al.
Abstract: Objective: To compare the effectiveness of a primary covid-19 vaccine series plus booster doses with a primary series alone for the prevention of hospital admission with omicron related covid-19 in the United States. Design: Multicenter observational case-control study with a test negative design. Setting: Hospitals in 18 US states. Participants: 4760 adults admitted to one of 21 hospitals with acute respiratory symptoms between 26 December 2021 and 30 June 2022, a period when the omicron variant was dominant. Participants included 2385 (50.1%) patients with laboratory confirmed covid-19 (cases) and 2375 (49.9%) patients who tested negative for SARS-CoV-2 (controls). Main outcome measures: The main outcome was vaccine effectiveness against hospital admission with covid-19 for a primary series plus booster doses and a primary series alone by comparing the odds of being vaccinated with each of these regimens versus being unvaccinated among cases versus controls. Vaccine effectiveness analyses were stratified by immunosuppression status (immunocompetent, immunocompromised). The primary analysis evaluated all covid-19 vaccine types combined, and secondary analyses evaluated specific vaccine products. Results: Overall, median age of participants was 64 years (interquartile range 52-75 years), 994 (20.8%) were immunocompromised, 85 (1.8%) were vaccinated with a primary series plus two boosters, 1367 (28.7%) with a primary series plus one booster, and 1875 (39.3%) with a primary series alone, and 1433 (30.1%) were unvaccinated. Among immunocompetent participants, vaccine effectiveness for prevention of hospital admission with omicron related covid-19 for a primary series plus two boosters was 63% (95% confidence interval 37% to 78%), a primary series plus one booster was 65% (58% to 71%), and for a primary series alone was 37% (25% to 47%) (P<0.001 for the pooled boosted regimens compared with a primary series alone). Vaccine effectiveness was higher for a boosted regimen than for a primary series alone for both mRNA vaccines (BNT162b2 (Pfizer-BioNTech): 73% (44% to 87%) for primary series plus two boosters, 64% (55% to 72%) for primary series plus one booster, and 36% (21% to 48%) for primary series alone (P<0.001); mRNA-1273 (Moderna): 68% (17% to 88%) for primary series plus two boosters, 65% (55% to 73%) for primary series plus one booster, and 41% (25% to 54%) for primary series alone (P=0.001)). Among immunocompromised patients, vaccine effectiveness for a primary series plus one booster was 69% (31% to 86%) and for a primary series alone was 49% (30% to 63%) (P=0.04). Conclusion: During the first six months of 2022 in the US, booster doses of a covid-19 vaccine provided additional benefit beyond a primary vaccine series alone for preventing hospital admissions with omicron related covid-19. Readers' note: This article is a living test negative design study that will be updated to reflect emerging evidence. Updates may occur for up to two years from the date of original publication.